Sosialisasi Upaya Meningkatkan Imunitas Tubuh Anak dalam Menghadapi Pandemi Covid-19 di Posyandu Mekar Sari - Widia Ningsih; Lastama Sinaga; Halim Simatupang; Ayu Putri Ningsih; Lisa Amalia; Fadhlan Musdary; Reza Maulana Ahmad Lubis; Joevan Houtten Nahampun (Universitas Lancang Kuning, 2022)
To prevent this transmission, it can be done by increase the body's immune system. The problem that occurs in the community is the lack of understanding of parents regarding the Covid-19 pandemic. This socialization was named Program Kemitraan Masyarakat (PKM) by Faculty of Mathematics and Natural Sciences of State University of Medan which was held at the Mekar Sari Posyandu. The aim of this socialization is to provide counseling and understanding to the community about the importance of maintaining and improving children's immunity in the face of the Covid-19 pandemic. The method of this socialization consists of preparation, implementation, and evaluation, solving. This socialization is carried out with a participatory educative approach by carrying out socialization of Covid-19 prevention